The Important of Mental Imagery in the Theory and Clinical Practice in the Solution-Focused Approach - Masahiro Kawahara (Research Developments in Medicine and Medical Science Vol. 3, 2023)
Recently, there has been a movement to apply mental imagery to psychological intervention techniques, focusing on the relationships among mental imagery, cognitive function, and emotional responses. In addition, there is a growing interest in the clinical application of mental imagery, with special features on cognitive therapy using mental imagery in research journals such as Memory or the Journal of Behavior Therapy and Experimental Psychiatry. Mental imagery plays an important role in the theory and practice of solution-focused approach(SFA) in brief psychotherapy. This chapter introduces my research that examines the impact of positive self-image about the future on emotional states using the time machine question of the SFA theory and shows that mental imagery also plays an important role in the theory and clinical practice of SFA.